2017
DOI: 10.1038/s41598-017-16809-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Synthetic Human SLURP-1 with the Nicotinic Acetylcholine Receptors

Abstract: Human SLURP-1 is a secreted protein of the Ly6/uPAR/three-finger neurotoxin family that co-localizes with nicotinic acetylcholine receptors (nAChRs) and modulates their functions. Conflicting biological activities of SLURP-1 at various nAChR subtypes have been based on heterologously produced SLURP-1 containing N- and/or C-terminal extensions. Here, we report the chemical synthesis of the 81 amino acid residue human SLURP-1 protein, characterization of its 3D structure by NMR, and its biological activity at nA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 36 publications
0
42
1
Order By: Relevance
“…In summary, Makaluvamine G might present a potentially useful hit molecule for the rational design of drugs acting like un-competitive antagonists of nAChRs and other Cys-loop receptors. This might be of special interest in the light of findings that endogenous nAChR ligands from the Ly6 family show some properties similar to un-competitive inhibitors [ 30 , 31 , 32 ]. Thus, small molecules mimicking properties of endogenous modulators of Cys-loop receptors could be of a high value.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, Makaluvamine G might present a potentially useful hit molecule for the rational design of drugs acting like un-competitive antagonists of nAChRs and other Cys-loop receptors. This might be of special interest in the light of findings that endogenous nAChR ligands from the Ly6 family show some properties similar to un-competitive inhibitors [ 30 , 31 , 32 ]. Thus, small molecules mimicking properties of endogenous modulators of Cys-loop receptors could be of a high value.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work on low molecular weight compounds (Kudryavtsev et al, 2018;Spirova et al, 2019), a-conotoxins (Kudryavtsev et al, 2015;Kasheverov et al, 2016;Kryukova et al, 2018a), and human Ly6 proteins (Lyukmanova et al, 2016;Durek et al, 2017), we found that some of them can bind to the orthosteric or allosteric sites of nAChRs. Here we did not plan a detailed investigation of the mechanism of oligoarginine action, but we made exceptions for R8 and W2R4.…”
Section: Discussionmentioning
confidence: 97%
“…Among the latter is SLURP-1 functioning as a water-soluble paracrine/autocrine messenger molecule which binds nicotinic acetylcholine receptors and regulates keratinocyte growth and angiogenesis. Such properties of SLURP-1 make it a valuable object to study as an endogenous cholinergic ligand similar to snake venom neurotoxins that played a crucial role in the nAChR research for decades [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, no experimental spatial structure of fusion SLURP-1 proteins were described. Fusion proteins demonstrated positive allosteric modulation of α7 nAChR while recombinant SLURP-1 act as an inhibitor of the receptor [8].…”
Section: Introductionmentioning
confidence: 99%